Experimental analysis of steel fiber reinforced concrete beams in shear - Nzambi,Aaron Kadima Lukanu Lwa (2022)
Abstract Some normative recommendations are conservative in relation to the shear strength of reinforced concrete beams, not directly considering the longitudinal reinforcement rate. An experimental program containing 8 beams of (100 x 250) mm2 and a length of 1,200 mm was carried out. The concrete compression strength was 20 MPa with and without 1.00% of steel fiber addition, without stirrups and varying the longitudinal reinforcement ratio. Comparisons between experimental failure loads and main design codes estimates were assessed. The results showed that the increase of the longitudinal reinforcement ratio from 0.87% to 2.14% in beams without steel fiber led to an improvement of 59% in shear strength caused by the dowel effect, while the corresponding improvement was of only 22% in fibered concrete beams. A maximum gain of 109% in shear strength was observed with the addition of 1% of steel fibers comparing beams with the same longitudinal reinforcement ratio (1.2%). A significant amount of shear strength was provided by the inclusion of the steel fibers and allowed controlling the propagation of cracks by the effect of stress transfer bridges, transforming the brittle shear mechanism into a ductile flexural one. From this, it is clear the shear benefit of the steel fiber addition when associated to the longitudinal reinforcement and optimal values for this relationship would improve results.